Proteoglycans in macrophages: characterization and possible role in the cellular uptake of lipoproteins. - Halvorsen, B (1998)
The murine macrophage cell line J774 was incubated with [35S]sulphate. The cell-associated 35S-labelled macromolecules were shown to be proteoglycans and glycosaminoglycans in similar amounts. The possible presence of cell-surface proteoglycans was investigated by incubating [35S]sulphate-labelled cells with trypsin for 15 min. The released material contained approx. 70% free glycosaminoglycan chains and 30% proteoglycans. The latter component was demonstrated by HNO2 treatment to contain heparan sulphate. In the total cell fraction not treated with trypsin a small but significant portion was shown to be chondroitin sulphate proteoglycan. The cell-associated glycosaminoglycans contained both chondroitin sulphate and heparan sulphate. To investigate possible biological functions of cell-surface proteoglycans in macrophages, cells were incubated with NaClO3 to inhibit sulphation of proteoglycans and beta-d-xyloside to abrogate proteoglycan expression. The uptake of oxidized 125I-tyraminylcellobiose-labelled low-density lipoprotein (125I-TC-LDL) was typically two to three times higher than that of native 125I-TC-LDL in untreated J774 cells. The cellular uptake at 37 degreesC of native 125I-TC-LDL was decreased 25% after both NaClO3 and xyloside treatment, whereas the uptake of oxidized 125I-TC-LDL was decreased 35% after both types of treatment. The mRNA levels for the scavenger receptor A-II and the LDL receptor were not affected by NaClO3 or xyloside treatment. Furthermore, fluid-phase endocytosis, measured as uptake of horseradish peroxidase, and receptor-mediated endocytosis, measured as uptake of 125I-TC-ovalbumin, were not affected by NaClO3 treatment of J774 cells. Removal of cell-surface chondroitin sulphate with chondroitinase ABC decreased only the binding of native 125I-TC-LDL, whereas removal of heparan sulphate with heparitinase decreased the binding of both oxidized and native 125I-TC-LDL. Addition of lipoprotein lipase increased the uptake of oxidized 125I-TC-LDL 1.7 times and the uptake of native 125I-TC-LDL 2.1 times. The binding of the former was more sensitive to NaClO3 treatment than the latter. The results presented support the notion that some of the uptake pathways for lipoproteins in the foam-cell-forming macrophages depend on the presence of cell-surface heparan sulphate and chondroitin sulphate.